Identification And Prevalence Of Flea In Feral Cats In Some Markets Sidoarjo District: Identifikasi Dan Prevalensi Pinjal Pada Kucing Liar Di Beberapa Pasar Kabupaten Sidoarjo - Purwa, Ajeng Acika; Ardiansyah, Syahrul (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Flea is ectoparasite that live outside the body of their host, one of which host is a cat. Flea infestation have potential to cause dermatitis or a abnormality skin known as flea allergic dermatitis. Cat is an animal that often interact with humans, one of them as a pet, so they have potential to transmit flea to human. The purpose of this study was to identify and determine the prevalence of flea in wild cat in several markets. Sample that used in this study are feral cats taken from the Larangan Market and Gading Fajar Market in Sidoarjo distric. The feral cats obtained were then examined for the presence and type of flea. The results of the examination showed that the prevalence of flea infection in feral cats in the Larangan Market was 81.8% and the Gading Fajar Market was 54.5%. The identification result showed that the fleas found in feral cats from the Larangan Market and Gading Fajar Market were all Ctenocephalides felis. The difference in prevalence is caused by the different environmental conditions in the two markets. A dirty environment has the potential to increase the number of cats infected with fleas.